INTERACTIVE METHODS AND THEIR IMPACT ON TEACHER LEARNING - Bakayeva Shoira Bakhshilloyevna (Western European Studies, 2024)
This article analyzes the role of interactive teaching methods in the educational process, their positive impact on student learning and their importance in improving educational effectiveness. The theoretical foundations of the methods, practical application experiences and results are discussed. The research examined the integration of modern educational technologies into biological science
Keywords: interactive methods; educational efficiency; modern pedagogy; biology